ISOLATION AND INVESTIGATION OF BACTERIA WITH LIPOLYTIC ACTIVITY FROM HOT SPRINGS IN THE NORTHERN BAIKAL REGION - K. N. Sorokina; A. S. Rozanov; A. V. Bryanskaya; S. E. Peltek (Вавиловский журнал генетики и селекции)
We have studied properties of bacterial strains isolated from hot springs in the Northern Baikal region, Baikal Rift Zone, known to have a wide range of growth conditions (pH, temperature, and carbon sources). The phylogenetic analysis and microbiological studies show that thermophilic strains belonging to the Geobacillus stearothermophilus,Anoxybacillus flavithermus, and Thermoactinomyces vulgaris species express lipolytic activity. The isolated Geobacillus stearothermophilus strains grow at up to 70 °С in a wide pH range (5–10). The isolates of the Anoxybacillus genus can grow at 60–70 °С and рН ≤ 11. Thermoactinomyces vulgaris Gus-2-1 has a narrower growth condition range: 50–60 °С and рН 7–10. Of the strains with lipolytic activity isolated in this study, Geobacillus stearothermophilus is the most promising for further studies of secreted lipases.